Trade, Labor Market Frictions, and Residual Wage Inequality across Worker Groups - Krishna, Pravin; Poole, Jennifer P; Senses, Mine Zeynep (American Economic Review, 2012)
Using a matched employer-employee data set, we study the effects of trade liberalization on wage dispersion in Brazil across heterogeneous worker groups, keeping in mind that the assignment of workers to firms may be non-random and determined by the time-invariant productivity of workers specific to the firms with which they are matched. We find differential effects of trade reform on residual wage inequality across worker groups. High education workers experience greater increases in wage dispersion relative to low education workers following trade liberalization. This finding is broadly consistent with the theoretical predictions that emerge from models with heterogeneous firms, heterogeneous workers, and labor market frictions.